Correlação entre peso corporal e volume renal por medidas lineares ultra-sonográficas em cães da raça Dachshund - Cunha, Lívia Maria Ferreira (2005)
Alterations in kidney shape and size are important clinical signs of renal disturbs. Kidney ultrasonography complements information obtained by clinical, laboratorial and radiographic exams, being of basic importance in the evaluation of nephropathies. The knowledge of normal Kidney size and anatomy of the dog is of great value, therefore the presence of alterations assists in the diagnostic and prognostic of renal diseases. The aim of this study was to determine kidney dimensions through ultrasonography of healthy Dachshund dogs and to make a correlation of these measures with body weight. Thirty Dachshund dogs (12 males and 18 females), adults, health, ranging in body weight from 4,8 to 12 kg and in age from one to eight years, were used. Ultrasonographic exam were realized to measure kidney linear measures through sagittal, transverse and dorsal plans of section to evaluate the length (L), width (W) and height (H). The Kidney volume (V) was estimated from these mean linear measures using the following formula for the volume of an ellipsoide: V =L x W x H x 0,523. The mean values of length, width, height and renal volume were respectively 4,59; 2,29; 2,42 cm; 13,69 cm3 for right kidney and 4,63; 2,42; 2,45 cm; 14,80 cm3 for the left. The left renal dimensions were significantly larger than the right one and also the males kidneys were larger than the females. The linear measures and renal volume were correlated to body weight and it was observed positive correlation between all the variables. Ultrasonography is a trusting method of easy application for measuring Kidney dimensions. It can be used safety to evaluate Kidney size.